2006
DOI: 10.1073/pnas.0602185103
|View full text |Cite
|
Sign up to set email alerts
|

Differential HIV-1 replication in neonatal and adult blood mononuclear cells is influenced at the level of HIV-1 gene expression

Abstract: The majority of HIV-1-infected neonates and infants have a higher level of viremia and develop AIDS more rapidly than infected adults, including differences seen in clinical manifestations. To determine the mechanisms of HIV-1 infection in neonates vs. adults, we compared the replication kinetics of HIV-1 in neonatal (cord) and adult blood T lymphocytes and monocyte-derived macrophages (MDM) from seven different donors. We found that HIV-1 replicated 3-fold better in cord blood T lymphocytes compared with adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…However, one clone also derived from patient 19, now designated the clone 19-18 LTR, exhibited a marginally lower basal level of transcription in Jurkat T cells but much lower basal transcription in U-937 cells, suggesting that LTR-mediated gene expression may be modulated by different transcription factors in a cell typedependent manner. This result is consistent with reports showing that different cells can affect the level of HIV-1 replication and gene expression owing to their distinct expression of cell typespecific transcription factors [31][32][33]. We have also reported herein that the 19-18 HIV-1 LTR clone did not respond to Tatmediated transactivation with strain IIIB Tat in Jurkat T cells and U-937 cells (Figure 2).…”
Section: Discussionsupporting
confidence: 82%
“…However, one clone also derived from patient 19, now designated the clone 19-18 LTR, exhibited a marginally lower basal level of transcription in Jurkat T cells but much lower basal transcription in U-937 cells, suggesting that LTR-mediated gene expression may be modulated by different transcription factors in a cell typedependent manner. This result is consistent with reports showing that different cells can affect the level of HIV-1 replication and gene expression owing to their distinct expression of cell typespecific transcription factors [31][32][33]. We have also reported herein that the 19-18 HIV-1 LTR clone did not respond to Tatmediated transactivation with strain IIIB Tat in Jurkat T cells and U-937 cells (Figure 2).…”
Section: Discussionsupporting
confidence: 82%
“…In 2011, there were 3.3 million children living with HIV and an estimated 330,000 children who became newly infected with HIV worldwide, primarily through mother-to-child transmission of HIV [2, 4]. In the United States, HIV/AIDS is ranked the third leading cause of death among women aged 25 to 44 years old and accounts for the most common cause of death among African-American women in this age group [5, 6]. Since the institution of antiretroviral therapy, the incidence of vertical transmission of HIV in the U.S. and other resource-rich countries has decreased significantly but continues to be a critical issue in resource-poor nations and among poor populations in resource-rich nations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that immune cells from neonates are more susceptible to HIV infection than those from adults [6, 21, 22]. It is likely that acute or chronic alcohol exposure can exacerbate neonatal cellular immune system defects.…”
Section: Introductionmentioning
confidence: 99%
“…However, genetic diversity in children from 0 to 2 year-old was significantly lower than in adults, which suggests that certain selection is acting on the virus variants that are vertically transmitted. After perinatal transmission, very high rates of HIV-1 replication have been detected in younger infected children that can persist for long periods of time, especially in untreated patients [25,62]. High rates of virus replication increase HIV-1B population sizes and, due to the error-prone nature of the HIV-1B polymerase, may result in random accumulation of mutations in the virus population.…”
Section: Discussionmentioning
confidence: 99%